Recent Approaches to Determine Static and Dynamic Redox State-Related Parameters - Cristina Mas-Bargues; Esther García-Domínguez; Consuelo Borrás (MDPI AG, 2022)
Oxidative stress refers to an imbalance between oxidant and antioxidant molecules, which is usually associated with oxidative damage to biomolecules and mitochondrial malfunction. Redox state-related parameters include (1) the direct measurement of ROS, (2) the assessment of the antioxidant defense status, and (3) the analysis of the resulting oxidative damage to molecules. Directly measuring ROS appears to be the preferred method among scientists, but most ROS are extremely unstable and difficult to measure. The processes of determining both the oxidative damage to biomolecules and the antioxidant system status, although both are indirect approaches, provide a reliable method to measure oxidative stress on a given sample. Recently, the Seahorse XF and the Oroboros O2k systems have provided new insights into the redox state from a more dynamic point of view. These techniques assess mitochondrial oxidative phosphorylation function and bioenergetics on isolated mitochondria, cultured cells, or specific tissues such as permeabilized fibers. This review describes a range of methodologies to measure redox state-related parameters, their strengths, and their limitations. In conclusion, all these techniques are valid and none of them can be replaced by another. Indeed, they have the potential to complement each other for a complete evaluation of the redox state of a given sample.